2022
DOI: 10.3390/ph15101282
|View full text |Cite
|
Sign up to set email alerts
|

4D Printing of Hydrogels: Innovation in Material Design and Emerging Smart Systems for Drug Delivery

Abstract: Advancements in the material design of smart hydrogels have transformed the way therapeutic agents are encapsulated and released in biological environments. On the other hand, the expeditious development of 3D printing technologies has revolutionized the fabrication of hydrogel systems for biomedical applications. By combining these two aspects, 4D printing (i.e., 3D printing of smart hydrogels) has emerged as a new promising platform for the development of novel controlled drug delivery systems that can adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 157 publications
(168 reference statements)
0
12
0
Order By: Relevance
“…It could be concluded that the spatially controlled volume transformation could be used as a means to induce shape deformation as a solid, as well as to release encapsulated molecules in a liquid. [ 48,49 ]…”
Section: Resultsmentioning
confidence: 99%
“…It could be concluded that the spatially controlled volume transformation could be used as a means to induce shape deformation as a solid, as well as to release encapsulated molecules in a liquid. [ 48,49 ]…”
Section: Resultsmentioning
confidence: 99%
“…4D printing has the potential to transform regenerative medicine by enabling the fabrication of living tissues and organs with the ability to alter their shape or qualities over time. Some applications of 4D printing in the aforementioned sector might include the following:  Tissue engineering: 4D printing could be used to create living tissue structures, such as blood vessels, skin, or muscle, that could be used to replace damaged or diseased tissue in the body (Tamay et al, 2019)  Scaffold free organ printing: 4D printing could be used to create functional organs, such as hearts, livers, or kidneys, using a patient's own cells, eliminating the need for scaffold materials (Langford et al, 2020)  Smart implants: 4D printed implants, such as artificial joints or heart valves, could be designed to change shape or properties over time, potentially extending the life of the implant and reducing the need for revision surgeries (Sahafnejad-Mohammadi et al, 2022)  Self-healing materials: 4D printed materials for medical applications could be designed to self-repair small tears or damages, potentially extending the life of the implant or scaffold (Wang et al, 2022)  Adaptive stents: 4D printing could be used to create stents that can adapt to changes in the body, such as expanding or contracting to fit the size of a blood vessel (Lin et al, 2020)  Drug delivery systems: Potentially increasing the efficacy of therapies, 4D printing could be utilized to construct medication delivery systems capable of controlled drug release (Tran et al, 2022;Aversa et al, 2016c) These are examples of the potential applications of 4D printing in regenerative medicine found in published literature and as the technology develops, it is likely that more and more creative uses will be found. However, it's worth noting that 4D printing technology is still in its infancy and it will be some time before it is utilized in clinical applications.…”
Section: D Printing Applicationsmentioning
confidence: 99%
“…43 At present, water-or humidity-sensitive materials are widely available, which has aroused the interest of researchers. [44][45][46] However, the current challenge is how to accurately control the expansion/contraction degree of the humidity-sensitive material in the process of shape deformation, so as to be more widely and better applied in engineering. Researchers often harness this natural response to design and develop innovative materials for applications in fields including cardiac engineering.…”
Section: Reviewmentioning
confidence: 99%